2018
DOI: 10.3389/fphar.2018.00372
|View full text |Cite
|
Sign up to set email alerts
|

1-Deoxynojirimycin (DNJ) Ameliorates Indomethacin-Induced Gastric Ulcer in Mice by Affecting NF-kappaB Signaling Pathway

Abstract: Gastric ulcer (GU) is a main threat to public health. 1-Deoxynojirimycin (DNJ) has antioxidant and anti-inflammatory properties and may prevent GU but related mechanism remains unclear. DNJ was extracted from the supernatants of Bacillus subtilis by using ethanol and purified by using CM-Sepharose chromatography. A GU mouse model was induced by indomethacin. The functional role of DNJ in GU mice was explored by measuring the main molecules in the NF-KappaB pathway. After the model establishment, 40 GU mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 73 publications
(76 reference statements)
1
22
1
Order By: Relevance
“…SP can promote the secretion of gastric acid and pepsin, lead to gastrointestinal contraction, increase the blood flow volume in the stomach, and aggravate gastric injury [ 23 ]. VIP can promote SS release from D cells, can further inhibit the secretion of gastric acid, and plays a positive role in the gastric injury [ 24 ]. When gastric injury happens, VIP level and SS secretion decline, leading to accelerated secretion of gastric acid and high gastric mucosa injury degree [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SP can promote the secretion of gastric acid and pepsin, lead to gastrointestinal contraction, increase the blood flow volume in the stomach, and aggravate gastric injury [ 23 ]. VIP can promote SS release from D cells, can further inhibit the secretion of gastric acid, and plays a positive role in the gastric injury [ 24 ]. When gastric injury happens, VIP level and SS secretion decline, leading to accelerated secretion of gastric acid and high gastric mucosa injury degree [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naito et al (1998) reported that the amounts of malondialdehyde (MDA) and myeloperoxidase (MPO) have increased, as for the levels of glutathione and its enzymes, superoxide dismutase (SOD), catalase (CAT) have decreased in damaged stomach tissue. While for Albayrak et al (2015) and Piao et al (2018) have noted that that the Indomethacin has changed the oxidant-antioxidant balance in stomach tissue, which includes MDA, MPO, GST, SOD, and CAT.…”
Section: Non-steroidal Anti-inflammatory (Nsai) Drugs Induced Peptic mentioning
confidence: 99%
“…The fi nancial resources, the end-point of the study, the hypothesis or the research question that has to be tested infl uence the fi nal choice of an experimental model. The preferred animal models used for researches on new agents for the treatment of gastric ulcer are experimental models based on factors influencing the humans' way of life: ulcer induced by ethanol (22) or NSAIDs (23).…”
Section: Discussionmentioning
confidence: 99%